Optimization and analysis of interior permanent magnet drive motor with unequal thickness magnetic poles for electric vehicle - Shilun MA; Yongyi WU; Changwei LI; Keqi CHEN (Journal of Hebei University of Science and Technology)
To enhance the output torque of permanent magnet drive motors for electric vehicles, while simultaneously reducing cogging torque and torque ripple, an interior permanent magnet motor with auxiliary slots in unequal thickness magnetic poles was proposed. Firstly, by analyzing the geometric relationships of unequal thickness magnetic poles, a mathematical model relating the radial air gap magnetic flux density of the rotor to the magnetic pole parameters was established. Secondly, using the energy method and Fourier analysis method, the relationship expression between rotor magnetic poles and cogging torque was formulated, deriving the influencing factors of unequal thickness magnetic poles and rotor auxiliary slots on cogging torque. Additionally, an analytical expression for the motor′s quadrature and direct-axis inductance was established through the equivalent magnetic circuit method, obtaining parameters that indicate the effects of unequal thickness magnetic poles and rotor auxiliary slots on output torque. Finally, with torque ripple, cogging torque, and output torque as optimization objectives, the particle swarm optimization algorithm was used to perform multi-objective optimization on the maximum magnetic pole thickness, minimum magnetic pole thickness, the width of magnetic pole, the depth and width of the rotor auxiliary slots, in order to determine the optimal parameters, and a prototype was then developed for experimental testing. The results indicate that the optimized motor has reduced torque ripple by 13.76%, decreased cogging torque by 51.7%, and increased output torque by 14.2%, validating the correctness of the theoretical calculations and simulation analysis. The proposed novel topology structure and its optimization design method can effectively enhance the output characteristics, providing certain theoretical references for the drive motor used in electric vehicles.